Penatalaksanaan Relaksasi Otot Progresif dan Pemberian Lilin Aromaterapi Lavender dengan Masalah Gangguan Pola Tidur pada Lansia Hipertensi di Desa Margo Mulyo - Putri Puspitasari; Tutik Yuliyanti (Indonesian Journal on Medical Science, 2022)
Signs and symptom that arise due to hypertension cause sleep pattern disturbances.Relaxation techniques that can be applied include progressive muscle relaxation and lavender aromatherapy candles. The purpose to describe the nursing management of sleep pattern disorders with progressive muscle relaxation and lavender aromatherapy candles in the elderly with hypertension. The design of this research is descriptive qualitative with a case study approach. The results of the study found that the subject said headaches, neck felt heavy, dizzy, shoulders felt heavy, had difficulty sleeping well, maintained sleep, started sleeping, sleep hours ± only 3.5 - 4 hours, woke up at night 3-5 times, tired after waking up, sleepy during the day, uncomfortable when sleeping and sometimes nightmares. The objective data: there are eye bags, the sclera is reddish white and area around eyes is black, the subject looks lethargic, BP: 160/100 mmHg - 170/100 mmHg, RR: 18 - 20 x/minute, N: 96 -98 x/min, S: 36 - 36.8ºC. The nursing diagnosis is sleep pattern disorders related to age and disease. Planning: teach progressive muscle relaxation and giving lavender atomotherapy candles. Nursing actions for 8 days with 7 actions. The evaluation the subject said that he was sleeping soundly, not disturbed, sleep was 4-5 hours, BP: 140/80 - 150/80 mmHg, the value of Insomnia Rating Scale: 23-24 (mild insomnia). Progressive muscle relaxation and lavender aromatherapy candles are effective for improving sleep quality but have not been able to overcome the problem of sleep pattern disorders.